Gradual Sewing Activities as an Effort to Improve Children's Fine Motor Skills at RA Nw Tanak Beak Barat - Hikmawati (MANDAILING GLOBAL EDUKASIA, 2025)
This study seeks to enhance the fine motor skills of early childhood learners through the implementation of structured and progressive sewing activities. Employing a classroom action research methodology, the study adopts the Kurt Lewin model, which consists of four systematic stages: planning, action, observation, and reflection. The research was conducted with Group A kindergarten students as the primary subjects. Data collection incorporated both qualitative and quantitative methods, utilizing observation and interview techniques to gather comprehensive insights into the children's motor skill development. The intervention involved introducing sewing activities in a gradual and developmentally appropriate manner, allowing children to build skills progressively over time. The findings of the study demonstrate a positive impact of gradual sewing activities on the development of fine motor skills among early learners. Observable improvements were recorded in each cycle, indicating consistent and significant progress in students' ability to perform tasks that require fine motor coordination. These enhancements were particularly evident in the children's increased precision, hand-eye coordination, and manual dexterity. Based on the results obtained, it can be concluded that gradual sewing activities represent an effective and practical strategy for supporting fine motor skill development in early childhood education. The structured nature of the activities, combined with their engaging and hands-on approach, makes them a valuable addition to the learning environment. As such, educators are encouraged to consider incorporating similar activities into early childhood curricula to foster motor development in a purposeful and enjoyable manner.